(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the opportunities and benefits of implementing Kaizen principles in improving business activity in the region. It shows how the main principles of the Kaizen approach - continuous process improvement, active employee participation, quality improvement and efficient use of resources - can be applied in small businesses and private entrepreneurs. The study developed practical recommendations for implementing the Kaizen model, taking into account regional economic conditions, existing problems and development prospects. The results show that the implementation of Kaizen principles is an important factor in improving the efficiency of business entities.